2009
DOI: 10.1177/1534734609334808
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Ipsilateral Reamputation in Patients with Diabetic Foot Lesions

Abstract: This study aimed to examine the rates and risk factors for ipsilateral re-amputation in 121 patients with diabetic foot and prior amputation. Twenty-six (21.5%) patients required re-amputation during a mean follow-up of 18 months. Most re-amputations were performed within the first 6 months of the initial amputation. Re-amputation was more common among patients in whom the initial amputation had only affected one or two toes. Age (hazard ratio: 1.06) and heel lesions (hazard ratio: 2.69) were significantly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 19 publications
5
50
2
Order By: Relevance
“…Some small studies have suggested higher age, DM, gangrene, previous revascularization, and smoking to be risk factors for reamputation. 14,18) In the present study, hemodialysis and a higher number of comorbidities were additional risk factors for the composite outcome.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Some small studies have suggested higher age, DM, gangrene, previous revascularization, and smoking to be risk factors for reamputation. 14,18) In the present study, hemodialysis and a higher number of comorbidities were additional risk factors for the composite outcome.…”
Section: Discussionmentioning
confidence: 89%
“…14) The reported proportion of patients with DM requiring reamputation is approximately 60%. [14][15][16][17][18] However, the risk factors for reamputation remain to be elucidated. The purpose of the present study was to identify risk factors for death and reamputation after LLA using a national inpatient database in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Risk of re-amputation is highest within the first 6 months of initial amputation (Izumi et al, 2006;Skoutas et al, 2009). A re-amputation rate of 21.5% within 18 months was reported by Skoutas et al (2009) and 1 year and 3 year rates of 26.7% and 48.3% by Izumi (2006). Forty percent of subjects with DM in a study by Tentolouris et al had an ipsilateral or contralateral amputation within an average of about 16 months of the first DM-related LEA (Tentolouris et al, 2004).…”
Section: Morbidity and Mortality Following Diabetes-related Lower Extmentioning
confidence: 99%
“…Re-amputation at a higher level on the residual limb is a function of disease progression, failure to heal, and risk factors that develop as a result of the initial amputation such as alteration in the pressure distribution on the residual weight bearing surface. Age and heel lesions have also been shown to be risk factors for re-amputation (Skoutas et al, 2009). Risk of re-amputation is highest within the first 6 months of initial amputation (Izumi et al, 2006;Skoutas et al, 2009).…”
Section: Morbidity and Mortality Following Diabetes-related Lower Extmentioning
confidence: 99%
See 1 more Smart Citation